The relationship between principal's leadership behavior and school climate in SMK Sibu Jaya / Mackencidy Ak Bujang - Bujang, Mackencidy (2015)
The aim of this study was to examine the relationship between principal's leadership behavior and school climate among secondary school teachers of SMK Sibu Jaya, Sarawak. The study focused on principal who led and run the school administration. The objectives of the study were: (a) to examine the nature of principal's leadership behavior as perceived by the secondary school teachers of SMK Sibu Jaya, Sarawak, (b) to examine the nature of school climate as perceived by the secondary school teachers of SMK Sibu Jaya, Sarawak and (c) to investigate the relationship between principal's leadership behavior and school climate among secondary school teachers of SMK Sibu Jaya, Sarawak. The methodology that was used in this study was Descriptive Correlation approach. The probability systematic sampling was used in this studyThe data were collected through questionnaire completed by 137 teachers in SMK Sibu Jaya, Sarawak. Quantitative data were collected from two instruments. The first instrument is The Multifactor Leadership Questionnaire (MLQ-5X) based on the Full Range Leadership Model developed by Bass and Avolio (2000). This instrument was used to measures leadership styles, and designates behaviors ranging from transactional leadership to transformational leadership. The second instrument is the OCDQ-RS (Hoy, Tarter, and Kottkamp, 1991; Kottkamp, Mulhern, and Hoy, 1987) which consists of 34 items. It has the capability to measure organizational climate based on 5 dimensions. The dimensions in the instrument were Supportive Behavior, Directive Behavior, Engaged Behavior, Frustrated Behavior, and Intimate Behavior. Based on research objectives of this study, the data were analyzed using descriptive and inferential statistics such as frequency analysis, descriptive analysis, and Pearson's Product Moment Correlation analysis.The results revealed that the relationship of principals' leadership behaviour and school climate is significantly positive. However, the result showed that the relationship with laissez faire and school climate was inverse relationship.